Kualitas Pelayanan Pengurusan Kartu Identitas Anak di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karo - Tarigan, Eva Riyanti; Wulandari, Novita; Simamora, Beltahmamero (Universitas Medan Area, 2024)
This writing aimed to assess the quality of services for processing Child Identity Cards at the Office of Population and Civil Registration of Karo Regency. The theory employed was Zeithaml’s five dimensions of service quality. Data were gathered through observations, interviews, documentation, triangulation, and analyzed qualitatively. The study concluded that overall the theory had been implemented, however two aspects of the theory had not been executed effectively. Supporting factors included good humans resources, si telu sada inovation, and clear service standards. Inhibiting factors consisted of inadequate facilities, infrastructure and personnel.